Telbivudine in liver transplant recipients: Renal protection does not overcome the risk of polyneuropathy and myopathy. Issue 8 (23rd June 2015) - Turan, Ilker; Yapali, Suna; Bademkiran, Fikret; Kose, Timur; Duman, Soner; Sozbilen, Murat; Gunsar, Fulya; Ersoz, Galip; Akarca, Ulus Salih; Ozutemiz, Omer; Karasu, Zeki
<x xml:space="preserve">Abstract</x> The recently reported benefit of telbivudine for renal function has not been systematically studied in long‐term liver transplantation (LT) recipients who are at high risk for renal impairment. We aimed to examine whether switching lamivudine therapy to telbivudine could improve renal function in LT recipients who have impaired renal function. This single‐center, prospective cohort study enrolled LT recipients who were on lamivudine for hepatitis B virus (HBV) prophylaxis and who had renal impairment for at least 1 year. Lamivudine was switched to telbivudine. The primary outcome was to evaluate the change in renal function at weeks 12, 24, 36, and 48. The secondary outcomes were to assess the efficacy of telbivudine for HBV prophylaxis and the safety profile of telbivudine in the posttransplant setting. After 45 patients were enrolled, the study was terminated early because of increased rates of polyneuropathy/myopathy. During telbivudine treatment (median, 64 weeks), estimated glomerular filtration rate (eGFR) increased in 34 patients (76%). The improvement in renal function was prominent after 24 weeks of telbivudine treatment. Telbivudine was effective as prophylaxis against HBV recurrence. Twenty‐six patients (58%) developed polyneuropathy and/or myopathy. The 1‐year estimated incidence of polyneuropathy/myopathy was 28%. Diabetes was the strongest predictor of polyneuropathy/myopathy (hazard ratio, 4.13; 95% confidence interval, 1.49‐11.50; P = 0.007). In conclusion, although it seems to have a favorable effect in the improvement of renal function and seems to be effective in the prevention of HBV recurrence, the high risk of polyneuropathy and myopathy hampers the use of telbivudine in LT recipients. Liver Transpl 21:1066‐1075, 2015. © 2015 AASLD.